THE EFFECTIVENESS OF MOBILE-ASSISTED LANGUAGE LEARNING (MALL) IN VOCABULARY DEVELOPMENT AMONG EFL LEARNERS - Odilova Gulzira (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
In an era dominated by digital technologies, Mobile-Assisted Language Learning (MALL) has become a cornerstone for enhancing vocabulary development in English as a Foreign Language (EFL) contexts. This article provides an in-depth synthesis of empirical research, including meta-analyses and localized studies, to evaluate MALL's impact on vocabulary retention, depth, and practical application. By integrating cognitive theories such as the spacing effect and dual-coding, it examines key affordances like gamification, adaptive personalization, and multimedia engagement, while critically assessing moderators including learner age, digital access, and intervention duration. Particular emphasis is placed on EFL environments in developing regions, such as Uzbekistan, where MALL addresses pedagogical gaps through hybrid models that combine mobile tools with traditional instruction. The analysis reveals consistent moderate-to-large effect sizes in vocabulary gains, advocating for MALL's broader adoption to promote autonomous, context-rich learning. Challenges like digital inequities are discussed, alongside recommendations for culturally adapted implementations to maximize efficacy in global EFL settings.